PENGARUH PROACTIVE PERSONALITY, TRAIT COMPETITIVENESS, DAN PHYSIOLOGICAL MECHANISM TERHADAP WELL-BEING DI INDUSTRY PERBANKAN - Lidya Permata Sari Gill; Netania Emilisa (Business, Economics dan Entrepreneurship, 2022)
The purpose of this paper is to examine the relationship between proactive personality, trait competitiveness, physiological mechanism, and well-being toward the employee in banking industry, specifically 2 banking company in Indonesia. This journal was using structural equation modelling (SEM) to analyze the variable and simple linear regression to test the hypothesis among the sample of 129 employees, google form were used to distribute the questioner which consists of 25 questions. The finding shows that proactive personality and trait competitiveness is positively related to well-being and for physiological mechanism is negatively related to well-being.